LOCAL WISDOM CERITA RAKYAT ‘SMONG’ SIMEULUE ACEH DARI SUDUT PANDANG KEBENCANAAN: MENINGKATKAN KESIAPSIAGAAN MASYARAKAT INDONESIA TENTANG MITIGASI BENCANA MEGATHRUST - Benardi, Andi Irwan; Amri, Yassirli (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
The Smong folklore from Simeulue, Aceh Province, represents a form of local wisdom that embodies community knowledge in natural disaster mitigation, particularly tsunamis. This traditional story highlights how indigenous knowledge plays a crucial role in preparing communities for potential megathrust disasters along the Sumatra Trench. The purpose of this study is to explore the role of Smong folklore in educating the people of Aceh and Indonesia about disaster preparedness and how these local values contribute to strengthening disaster mitigation efforts. This research employs a qualitative approach, with a literature review as the primary method of analysis. The findings indicate that the Smong folklore contains essential mitigation elements that remain highly relevant in contemporary disaster management. The story serves as a powerful educational tool to enhance public awareness and preparedness for major earthquakes, including megathrust disasters. By integrating traditional knowledge with modern disaster response strategies, communities can develop a more resilient approach to disaster preparedness. This study underscores the importance of preserving and promoting local wisdom in disaster education to minimize future risks and improve community resilience.